2009
DOI: 10.1186/cc8206
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and lung delivery of PDDS-aerosolized amikacin (NKTR-061) in intubated and mechanically ventilated patients with nosocomial pneumonia

Abstract: IntroductionAminoglycosides aerosolization might achieve better diffusion into the alveolar compartment than intravenous use. The objective of this multicenter study was to evaluate aerosol-delivered amikacin penetration into the alveolar epithelial lining fluid (ELF) using a new vibrating mesh nebulizer (Pulmonary Drug Delivery System (PDDS), Nektar Therapeutics), which delivers high doses to the lungs.MethodsNebulized amikacin (400 mg bid) was delivered to the lungs of 28 mechanically ventilated patients wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
98
1
5

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 119 publications
(105 citation statements)
references
References 24 publications
1
98
1
5
Order By: Relevance
“…Indeed, the gas and thus the aerosol delivered at the end of insufflation do not reach the deep part of the lungs. 7,15 An ideal algorithm would start nebulization immediately before the start of insufflation (this concerns only fully controlled ventilation) for the nebulizer flow to be highest at the beginning of insufflation. As the particle sizes produced by jet nebulizers decrease with increasing nebulizer flow, such an algorithm would allow production of the finest droplets at the beginning of inspiration, thus favoring distal lung deposition.…”
Section: Mechanisms Of Asynchrony and Implication For System Designmentioning
confidence: 99%
“…Indeed, the gas and thus the aerosol delivered at the end of insufflation do not reach the deep part of the lungs. 7,15 An ideal algorithm would start nebulization immediately before the start of insufflation (this concerns only fully controlled ventilation) for the nebulizer flow to be highest at the beginning of insufflation. As the particle sizes produced by jet nebulizers decrease with increasing nebulizer flow, such an algorithm would allow production of the finest droplets at the beginning of inspiration, thus favoring distal lung deposition.…”
Section: Mechanisms Of Asynchrony and Implication For System Designmentioning
confidence: 99%
“…Luyt et al 46 similarly showed favorable amikacin concentrations in ELF in a study of 28 mechanically ventilated patients with gram-negative VAP. In this study, patients received nebulized amikacin through an advanced nebulizer system as an adjunct to IV therapy.…”
Section: Alternative Dosing Strategies: Nebulizationmentioning
confidence: 86%
“…PK studies reporting antibiotic concentrations in the lung compartments using nebulization are becoming increasingly reported. 45,46 Athanassa et al 45 evaluated 20 critically ill patients with ventilator-associated tracheobronchitis treated with nebulized colistin. After the first nebulization, the median ELF concentrations were 6.7 and 2.0 mg/L at 1 and 8 hours, respectively.…”
Section: Alternative Dosing Strategies: Nebulizationmentioning
confidence: 99%
See 2 more Smart Citations